On the Foundations of Statistical Nuclear Physics - Syros, C. (HNPS Advances in Nuclear Physics, 2020)
The density matric for the nucleus, the canonical ensemble in second quantized mechanical definition of the temperature have from Quantum Field Theory. The evolution conservative or dissipalive form and is ergodic.